The European Union and the Caribbean Region: Situating the Caribbean Overseas Countries and Territories - Sutton, Paul (European Review of Latin American and Caribbean Studies, 2012)
Abstract:This paper examines one important dimension of the European Union's (EU) 'regional' engagement with the Caribbean: its relations with the Overseas Countries and Territories (OCT), with a particular focus on the possibility of furthering the policy goals of greater regional integration and cooperation. It does so in three parts. The first sets out the basis for current EU policy to the OCT which has been under discussion between the EU, the OCT and the four EU member states most involved (Denmark, France, the Netherlands and the United Kingdom) since 2008. It reports EU proposals for change and the responses to them by the Caribbean OCTs. The second part examines EU policy toward promoting greater regional cooperation among the Caribbean OCTs and between them and some of the other Caribbean regional organizations. Three distinct frameworks for cooperation and integration are discussed: with independent states as established in the Caribbean Community, the Caribbean Forum and the Economic Partnership Agreement; with the French departments and collectivities; and with the Caribbean OCT. In each the position of the Caribbean OCT is situated. The final part briefly discusses the creation of a 'new' framework for regional cooperation specific for the Caribbean OCT which will most closely match their interests in the Caribbean.Resumen: La Unión Europea y la Región del Caribe: Situando a los Países y Territorios de Ultramar del CaribeEste ensayo analiza una dimensión importante de la Unión Europea (UE) 'regional' y su compromiso con el Caribe: de igual manera sus relaciones con los Países y Territorios de Ultramar (PTU), con un enfoque particular sobre la posibilidad de promover los objetivos de la política con una mayor integración regional y cooperación. Este proceso se desglosa en tres partes. La primera establece la base para la actual política de la UE hacia los PTU, ya que esta ha sido objeto de debate entre los mismos y los cuatro miembros de la UE, donde Dinamarca, Francia, los Países Bajos y el Reino Unido son las más involucrados desde el 2008. En esta se informa la propuesta de la UE para el cambio y sus respuestas por los PTU del Caribe. La segunda parte examina la política de la UE hacia la promoción de una mayor cooperación regional entre los PTU del Caribe y otras organizaciones regionales del Caribe. Se discuten tres marcos distintos para la cooperación y la integración: con estados independientes establecidos en la Comunidad del Caribe, el Foro del Caribe y el Acuerdo de Asociación Económica, con los departamentos y colectividades franceses, y con los PTU del Caribe. En cada marco la posición de la PTU Caribe es clara. La parte final analiza brevemente la creación de un 'nuevo' marco específico para la cooperación regional para la PTU Caribe que con seguridad ajustaran sus intereses en el Caribe.